THE PHENOMENON OF FORM AND CONTENT IN HALIMA KHUDOYBERDIYEVA’S WORk - Nasiba Kurbanbayeva (European Journal of Humanities and Educational Advancements, 2023)
In the article, the phenomenon of form and content is highlighted through the works of Halima Khudoyberdiyeva.